Current status and potential role of goats in food security of India - Singh, M. K.; Verma, A. K.; Singh, S. K. (Indian Farming, 2018)
The goat population is gradually increasing around the world including India, mainly due to two reasons (i) universal acceptance of its meat and milk by the all the sections of society; and (ii) Potential and uniqueness goat milk in human nutrition and medicine, besides general food values. Goat and goat products have been playing crucial role in sustaining income and nutrition of most down trodden people particularly in disadvantageous regions. Production of per liter goat milk in India is cheaper than cow or buffalo milk, however, it’s collection, processing, value addition and marketing not yet commercially taken place. Goat milk, milk and meat products have huge demand in India and abroad. With an increase in demand for low-fat red meat alternatives by consumers, the future of the goat meat industry looks promising. The diverse and vast genetic pool offers a rapid method for improving traits of economic importance. Goats reared under intensive and semi-extensive systems showed better milk and meat productivity, dressing percentages and muscle-to-bone ratios as compared to those kept under extensive systems of feeding management. The improvement-cum-development programme are necessary to improve goat-based nutritional security and income of goat keepers likewise adoption of prophylactic measures (Goat Health Calendar); well-structured grading up programme; development of genetic stock by breeding with high potential bucks for dairy and meat breeds; capacity building of goat farmers to increase adoption of improved management practices. (breeding, nutrition, management, health care, marketing and economics of goats for different production systems); development of feeding resources at villages by improving wasteland and community pastures; strengthening and regularization of goat marketing structures; and value addition of goat products to increase income of goat farmers and nutritional status of all human beings.